Clinical characteristics of myasthenia gravis patients with coexistence of AChR and titin antibodies - Wang, Siqi; Shi, Difang; Wu, Shanshan; Zhang, Qijie; Xiao, Weiwei; Qian, Fang; Zheng, Yan; Bao, Jianjian; Liu, Jia; Chu, Xujun; Du, Kang (Frontiers in Neurology, 2025)
ObjectiveThis study aimed to investigate the clinical characteristics of patients with myasthenia gravis (MG) who are double-seropositive for acetylcholine receptor antibodies (AChR-Ab+) and titin antibodies (Titin-Ab+).MethodsA retrospective analysis was conducted on MG patients hospitalized in the Department of Neurology between March 2020 and June 2024. Patients were categorized into two groups based on antibody profiles: those with AChR antibody positivity alone and those with dual positivity for AChR and titin antibodies. Clinical features, MG classification, and treatment outcomes were compared between the two groups.ResultsA total of 35 MG patients were included, comprising 18 with single AChR-Ab+ and 17 with AChR-Ab+/Titin-Ab+. The dual antibody-positive group showed a significantly higher proportion of patients with MGFA classification above Class II (47.1%) and a higher rate of thyroid dysfunction (50%) compared to the single antibody-positive group (p = 0.001). The median age of onset in the dual antibody-positive group was older than that in the single antibody-positive group (67.0 years vs. 58.5 years), although this difference was not statistically significant (p > 0.05). No significant differences were observed between the two groups in terms of gender, initial symptoms, clinical manifestations, thymic hyperplasia, proportion of thymoma, treatment regimens, or therapeutic outcomes (all p > 0.05).ConclusionThis study provides the first systematic characterization of the clinical profile of AChR-Ab+/Titin-Ab+ myasthenia gravis patients in Southwest China. Our findings indicate that dual antibody-positive MG patients are more prone to generalized disease involvement and have a higher susceptibility to thyroid dysfunction.